THE RELATIONSHIP BETWEEN TIKTOK EWOM AND HO CHI MINH CITY STUDENTS’ STUDY-ABROAD INTENTION - Lam Mong Nghi; Hoang Minh Thu; Pham Khanh Phuong Tam; Hoang Vu Thanh Tam; Nguyen Ha Thuy Linh; Nguyen Tan Khang (Departemen Ilmu Komunikasi Universitas Andalas, 2026)
TikTok has developed as a valuable eWOM source for study abroad information. However, research looking specifically at the relationship between eWOM on TikTok and study abroad intentions is still lacking in Vietnam, particularly when it comes to the distinctive context of Ho Chi Minh city students. Purpose: This research focuses on defining the correlation between Ho Chi Minh city students’ study abroad intentions, and online word-of-mouth about study abroad content on TikTok platform. Method: This research uses a descriptive quantitative method of analysis. 384 students in Ho Chi Minh City universities and colleges constitute the data set of a structured questionnaire survey. Features of eWOM such as information quality, credibility, needs, usefulness, adoption level and attitudes towards information are evaluated by statistical analysis, including mean, standard deviation and Pearson correlation coefficient. Result: eWOM content regarding study abroad on TikTok had a favorable response by students. Information’s usefulness received the highest rating among the analyzed variables, and students’ attitudes towards along with the acceptance of study abroad eWOM content on TikTok tended to be positive. However, information credibility scored the lowest on average, showing the fact that students’ suspicion about the reliability and completeness of these content. Conclusion: TikTok functions mostly as an additional source, even if it is growing progressively more crucial in informing students about study abroad options and influencing their opinions. Implications: This research demonstrates that authentic and trustworthy content is more important and successful than traditional advertising approaches in influencing student choices.